Influence of the conditions of time and storageon dimensional stability of casts made from Irreversible hydrocolloid - Roca-Sacramento, Carlos (2018)
Objective: To evaluate the dimensional changes of casts from impressions with irreversible hydrocolloid (alginate) under different emptying times and storage conditions. Methods: In vitro experimental study that made 130 impressions with irreversible hydrocolloid (Tropicalgin ®) on a master model. The impressions were assigned in 13 groups depending on the emptying time (five, ten and 15 minutes), according to the storage conditions (use of cotton and/or sealed bags) and combining the conditions with the emptying times. The measurements of the models (height and diameter) were compared with the measurements of the master model to calculate the dimensional changes. Results: Related to height, a dimensional change of 0.3 ± 0.22 mm was obtained with the use of cotton rolls, hermetic sealing and emptying at 15 minutes (thirteenth group), while with immediate emptying (first group) a change of 0.41 ± 0.38 mm (p= 0.03), being these the groups with mostdimensional changes. Regarding the diameter level, the dimensional change of the thirteenth group was 0.08 ± 0.12 mm; while the first group was 0.06 ± 0.04 mm (p= 0.41). Conclusions: The groups of models with impressions stored with cotton rolls and hermetic packs showed the smallest dimensional changes at 5, 10 and 15 minutes of emptying time. The models obtained with the emptying times at 10, 15 minutes and without storage conditions showed the greatest dimensional changes in both height and diameter.